2019
DOI: 10.12928/telkomnika.v17i2.9450
|View full text |Cite
|
Sign up to set email alerts
|

A rapid classification of wheat flour protein content using artificial neural network model based on bioelectrical properties

Abstract: A conventional technique of protein analysis is laborious and costly. One rapid method used to estimate protein content is near infrared spectroscopy (NIRS), but the cost is relatively expensive. Therefore, it is necessary to find a cheaper alternative measurement such as measuring the bioelectrical properties. This preliminary study is a new rapid method for classified modeling of wheat flour protein content based on the bioelectrical properties. A backpropagation artificial neural network (ANN) was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(24 reference statements)
0
4
0
2
Order By: Relevance
“…Selain pengenalan pola objek, kecerdasan buatan juga mampu melakukan identifikasi terhadap suara seperti pengenalan suara dengan jenis bahasa arab [6], kemudian identifikasi video secara realtime [7]. Selanjutnya mengklasifikasikan kandungan protein dari tepung terigu [8].…”
Section: Pendahuluanunclassified
“…Selain pengenalan pola objek, kecerdasan buatan juga mampu melakukan identifikasi terhadap suara seperti pengenalan suara dengan jenis bahasa arab [6], kemudian identifikasi video secara realtime [7]. Selanjutnya mengklasifikasikan kandungan protein dari tepung terigu [8].…”
Section: Pendahuluanunclassified
“…Studying the prediction of moisture content and water activity of semi-finished cassava crackers using ANNs, Lertworasirikul & Tipsuwan (2008) concluded that the best one was the network with the 3-9-2 configuration, presenting RMSE of 0.0917 and correlation of 0.99. Sucipto et al (2019), seeking to classify the protein content of wheat flour from its bioelectric properties (capacitance and resistance) found that the best RNA topology for classification between hard, medium and soft flour of protein content is 2-20-50-3, which produced RMSE values of 0.0097 and 0.0399 and a correlation of 0.99 and 0.98 for the learning and verification stages, respectively.…”
Section: Evaluation Of the Best Ann Architecturesmentioning
confidence: 99%
“…used the ANN to estimate the firmness of kiwifruit having as inputs the concentrations of different nutrients in the fruits (N, K, Ca and Mg),while Sartori, et al (2017) proposed models of artificial neural networks to predict the effects of different operational variables (peroxidation time, temperature, pH, peroxide dosage and initial ° Brix) on the removal of color and sucrose content of sugarcane juice clarified.Mutlu, et al (2011) predicted 10 different quality properties of wheat flours combining near infrared reflectance spectroscopy (NIR) with the artificial neural networkand Sucipto, et al (2019) …”
mentioning
confidence: 99%
“…The same research states that ANN is faster and has a high degree of accuracy in making [7], [8]. So that ANN is inside [9], states that the model describes a systematic model in the learning process from input and output [10]. In the prediction case, the ANN model can be developed to produce optimal predictive results based on performance which is influenced by the amount of data used [11].…”
Section: Introductionmentioning
confidence: 99%